Networking, Small Farms and EU Rural Development Policy. (April 2014) - Peters, Rob; Gregory, Michael
Summary The European Network for Rural Development and National Rural Networks form part of the EU policy framework. They engage different stakeholder groups to promote knowledge development, cooperation and exchange. To date, small farm issues have been considered mainly within the context of thematic analyses, such as environmental services and short supply chains. The 2014–20 Common Agricultural Policy will offer Member States with many small farms the possibility of developing sustainable 'pathways of development' for farming communities. Under Pillar I there will be a simplified, optional, direct payments regime for small farms. In the rural development programmes, possible ways to support small farms include restructuring and modernisation, tackling generational renewal, measures for food chain integration and other revenue generation opportunities. Environmental priorities can also be tailored towards small farmers, such as methods for collective nature conservation services. Involving farmers in decision‐making processes promotes local commitment to development actions and support is tailored to local need. The challenge for EU rural networking activities therefore, will be to improve links between small farmers and the administrations to ensure that benefits are realised. Effective knowledge transfer between stakeholders will be further developed through increased use of social media whilst traditional networking tools will continue to be needed.